Do weight categories prevent athletes from the relative age effect? a meta-analysis of combat sports - Albuquerque, M. R.; Fukuda, D. H.; Da Costa, V. T.; Calábria Lopes, M. (Sport Sciences for Health, 2016)
The relative age effect (RAE) has been thoroughly examined and shown in many sporting contexts, and the grouping of athletes into weight categories may provide a partial solution to this problem. Thus, the aim of this meta-analysis was to verify if weight categories used in combat sports prevent athletes from the RAE, including an analysis separating the athletes by sex. After initially identifying 141 studies, 135 were excluded. The birth dates of combat sports participants in six studies were used to perform a meta-analysis. Odds ratios and 95 % confidence intervals were calculated. The main result of this investigation was the presence of RAE male and female groups and the male-only group of senior (professional/Olympic) athletes, but not the female-only group of senior and cadet or junior athletes. Thus, the RAE in combat sports is more prominent at the senior level and in male compared to female combat sports athletes. ABSTRACT FROM AUTHOR